IDeologI FeMInIs Dan RelIgIusItas MaDonna DalaM VIDeo MusIk “lIke a PRayeR” - Ellys Lestari Pambayun (Jurnal Ilmu dan Budaya, 2010)
Madonna had her success fought against the patriarchy system of Italian towards her heroism image of women. By means of Postmodern-Feminism, she improved the gender and race represented in her interaction with traditional hegemonic racism which removed the representation of women’s image.